Evaluation of amino acid profile in serum of patients with COVID-19 for providing a new treatment strategy : The amino acid profile in patients with COVID-19 - Ozturk, Ali; Bayraktar, Nihayet; Bayraktar, Mustafa; İbrahim, Bashar; Bozok, Taylan; Resat Ceylan, Mehmet (Journal of Medical Biochemistry, 2022)
Objective: Amino acids have an important role in metabolism and may affect COVID-19-related outcomes. Our study, the amino acid serum level of hospitalized COVID-19 patients was evaluated for determining new treatment strategy.Methods: The amino acid profile covering 43 amino acids in 68 subjects, comprising 30 (14 men and 16 women) controls and 38 (16 men and 22 women) COVID-19 patients, were examined. In addition, the amino acid profiles of the participants were screened by LC-MS/MS.Results: Compared with the control group, serum levels of 27 amino acids increased in the patient group. Alpha diaminopimelic acid, sarcosine, and hydroxyproline amino acids were considerably higher in the control group than in the patient group (p
Keywords: Amino acid; COVID-19; SARS-CoV-2; Treatment strategy